Visuel du Fespaco 2023 : regard de la sémiotique visuelle - Fidèle TIAMASSA (Revue Hybrides)
African countries are experiencing multiple crises. Their consequence is the lead of development processes. The resolution of these crises requires scientific questions which propose keys for their definitive management. This reflection on the visual of Fespaco 2023 by means of visual semiotics is part of this perspective. Our objective, first, is to demonstrate that this visual summons African history in a crisis situation. Secondly, it is a question of proving that the elements of the visual are in themselves keys to resolving crises in Africa. The resources to reduce them are endogenous and it is necessary to scrutinize them to identify their quintessence. For this, visual semiotics is adapted to the analysis of the different components of the visual. It will be a question of describing the constituents of the visual, taking into account their context of existence and production, and interpreting them. This approach is based on three levels of the sign: iconic, plastic, and linguistic. Their involvement gives convincing results in terms of the content of the visual. We remember that the crises experienced by African countries have existed in the past, and endogenous solutions have been peace solutions. Resorting to African values, including resilience and solidarity, is the key to a lasting solution to multifaceted crises. This is how Africa will be able to restore its image after centuries of cultural, economic and military occupation.